Strain-engineered growth of two-dimensional materials - Geun Ho Ahn; Matin Amani; Haider Rasool; Der-Hsien Lien; James P. Mastandrea; Joel W. Ager III; Madan Dubey; Daryl C. Chrzan; Andrew M. Minor; Ali Javey (Nature Communications, 2017)
Strain engineering is an essential tool for modifying local electronic properties in silicon-based electronics. Here, Ahn et al. demonstrate control of biaxial strain in two-dimensional materials based on the growth substrate, enabling more complex low-dimensional electronics.